The Role of Digital Art in Advancing Justice and Equality in Indonesia’s Artistic Communities (Indonesian Art and Justice Review, 2024)
With the rapid advancement of technology and the rise of digital platforms, digital art has emerged as a powerful tool for promoting justice and equality in Indonesia’s artistic landscape. This paper explores how digital art, from online exhibitions to virtual activism, has democratized access to artistic expression, enabling marginalized groups to share their voices and challenge societal norms. It examines the ways in which digital art allows for greater inclusivity, especially for underrepresented communities such as rural artists, LGBTQ+ individuals, and indigenous peoples. By focusing on several case studies of digital art projects and online campaigns, the paper analyzes how the digital sphere offers new avenues for political expression, social justice advocacy, and global solidarity.